Composite early strength agent as well as preparation method and application thereof
By preparing composite early strength agents, using the combination of fly ash, semi-water gypsum, calcium carbide slag and polycarboxylic acid water reducing agents, the problem of low early strength of alkali-activated gelling materials was solved, and the early strength was greatly improved and the later strength was significantly improved.
Patent Information
- Application Number
- CN202510365739.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-26
- Publication Date
- 2025-07-18
AI Technical Summary
There is a problem of low strength in early alkali-excited gelling materials using sodium sulfate as the exciter and slag as the precursor.
Fly ash, semi-water gypsum, calcium carbide slag, triethanolamine and polycarboxylic acid water reducing agent are used as raw materials to prepare composite early strength agents through grinding, heating reaction and grinding steps to promote ion dissolution and the formation of ettringite precursor substances and improve reaction activity.
In sodium sulfate-activated slag gelling materials, the hydration induction period is shortened, the early strength is improved and the hydration process is accelerated, the intensity is increased by more than doubled by 1d, and the intensity is increased by more than 50% in 28d.
Smart Images

Figure BDA0005329955720000041 
Figure BDA0005329955720000121 
Figure BDA0005329955720000131
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of admixtures for building materials, and particularly relates to a composite early-strength agent, a preparation method thereof, and an application thereof. Background Art
[0002] With the rapid development of the economy and the construction industry, the demand for ordinary Portland cement has gradually increased. However, the production of cement not only consumes a large amount of resources but also generates a large amount of CO2. Research shows that in global carbon emissions, the amount of CO2 generated during the cement production process accounts for about 5%-7% of the total carbon emissions. Therefore, reducing the total carbon emissions in the field of cement concrete has great practical significance for reducing global carbon emissions.
[0003] Alkali-activated cementitious materials (AAS), as a new type of green building material, are prepared by using amorphous aluminosilicate powder through an alkaline activator. As one of the most promising cement substitutes, AAS has received extensive attention in the past few decades. However, due to problems such as high raw material costs, large volume shrinkage, and significant increases in carbon emissions caused by the use of a large amount of strong alkali activators, researchers have gradually turned their attention to weak alkali activators with lower costs and smaller carbon footprints, and sodium sulfate is one of the representatives. The existing alkali-activated cementitious system using sodium sulfate as an activator and slag as a precursor performs well in terms of late mechanical properties, volume stability, carbon emissions, and raw material costs, but still has problems of low early setting strength and slow strength development. Summary of the Invention
[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defect that the existing alkali-activated cementitious material using sodium sulfate as an activator and slag as a precursor still has low early strength, so as to provide a composite early-strength agent, a preparation method thereof, and an application thereof.
[0005] The present invention provides a preparation method of a composite early-strength agent, comprising the following steps:
[0006] 1) Weigh raw materials, the raw materials include: fly ash, hemihydrate gypsum, carbide slag, triethanolamine, polycarboxylate superplasticizer, and water;
[0007] 2) Mix fly ash, hemihydrate gypsum, and carbide slag, add triethanolamine and grind to obtain a ground powder;
[0008] 3) Mix the ground powder obtained in step 2) with water and heat for reaction to obtain a reaction slurry;
[0009] 4) Mix the reaction slurry obtained in step 3) with a polycarboxylate superplasticizer, and then grind to obtain the composite early-strength agent.
[0010] Preferably, the raw materials in step 1), by weight, include: 12-16 parts of fly ash, 1-4 parts of hemihydrate gypsum, 1-4 parts of carbide slag, 0.8-1.5 parts of triethanolamine, 0.6-0.8 parts of polycarboxylate superplasticizer, and 75-85 parts of water;
[0011] The content of Al2O3 in the fly ash is ≥30 wt%;
[0012] In the present invention, fly ash with a specific Al2O3 content can be selected, and there is no need to specifically limit the content of other components in the fly ash. Optionally, the content of Al2O3 in the fly ash is 30 wt%-40 wt%;
[0013] In the present invention, there is no need to specifically limit the polycarboxylate superplasticizer, and a conventional polycarboxylate superplasticizer in the art can be used, which can be obtained commercially. Optionally, the solid content of the polycarboxylate superplasticizer is 35-60%. Further optionally, the polycarboxylate superplasticizer is selected from the polycarboxylate high-performance superplasticizer of Jiangsu Bote New Materials Co., Ltd.;
[0014] The content of Ca(OH)2 in the carbide slag is ≥70 wt% and the moisture content is ≤3 wt%.
[0015] In the present invention, carbide slag with specific Ca(OH)2 content and moisture content can be selected, and there is no need to specifically limit the content of other components in the carbide slag. Optionally, the content of Ca(OH)2 in the carbide slag is 70 wt%-90 wt% and the moisture content is 2-3 wt%.
[0016] Preferably, the median particle size of the ground powder in step 2) is not greater than 12 μm;
[0017] Optionally, the median particle size of the ground powder in step 2) is 10-12 μm;
[0018] Optionally, the grinding is selected from ball milling.
[0019] Preferably, the temperature of the heating reaction in step 3) is 50-70 °C and the heating reaction time is 24-48 h;
[0020] Optionally, the heating reaction is carried out under stirring conditions, and the stirring speed is 100-200 rpm;
[0021] The reaction rate of the fly ash in step 3) is ≥60%;
[0022] Optionally, the reaction rate of the fly ash in step 3) is 60-70%.
[0023] Preferably, in step 4), it is ground to a median particle size not greater than 6 μm;
[0024] Optionally, the grinding is selected from ball milling.
[0025] Optionally, in step 4), the grinding is carried out until the median particle size is 5 - 6 μm.
[0026] Preferably, after the grinding step in step 4), there is also a step of adjusting the solid content;
[0027] Optionally, after the grinding step in step 4), the solid content is adjusted to 18 - 22%, and the composite early strength agent is obtained.
[0028] The present invention provides a composite early strength agent prepared by the preparation method of the above-mentioned composite early strength agent.
[0029] The present invention provides a sodium sulfate-activated slag cementitious material, which includes the above-mentioned composite early strength agent.
[0030] Preferably, the mass content of the composite early strength agent in the sodium sulfate-activated slag cementitious material is 3 - 5 wt%.
[0031] The present invention also provides an application of the above-mentioned composite early strength agent or the above-mentioned sodium sulfate-activated slag cementitious material in building materials.
[0032] The technical solution of the present invention has the following advantages:
[0033] The preparation method of the composite early strength agent provided by the present invention includes the following steps: 1) Weigh the raw materials, and the raw materials include: fly ash, hemihydrate gypsum, carbide slag, triethanolamine, polycarboxylate water reducer and water; 2) Mix fly ash, hemihydrate gypsum and carbide slag, add triethanolamine and grind to obtain ground powder; 3) Mix the ground powder obtained in step 2) with water and heat for reaction to obtain a reaction slurry; 4) Mix the reaction slurry obtained in step 3) with polycarboxylate water reducer, and then grind to obtain the composite early strength agent. Each raw material used in the present invention, fly ash is rich in Al 3+ , hemihydrate gypsum is rich in SO4 2- , carbide slag is rich in Ca 2+ , and the formed solution is alkaline, which can provide OH -, after the raw materials of these specific ions used in the present invention are ground (ultrafined) in step 2), their internal activity is more easily excited, and by methods such as using carbide slag to increase alkalinity and triethanolamine to promote ion dissolution, the surface structure of fly ash is destroyed, further inducing the dissolution of aluminum ions and promoting the acceleration of hydration; then under the heating reaction in step 3), the ion dissolution rate inside the raw materials is accelerated, forming a precursor substance of ettringite with early strength enhancing effect. Then through the wet grinding process in step 4), under the action of mechanical force, the reaction activity of each raw material in this early strength agent is enhanced, and it is further transformed into the final product of ettringite crystals. The reaction equation for the formation of ettringite is as follows:
[0034]
[0035] Finally, the composite early strength agent is obtained. Adding the composite early strength agent obtained by the specific method of the present invention into the sodium sulfate-activated slag system can effectively induce the formation of products in this system, shorten the hydration induction period, and thus improve its early strength, playing a role in accelerating hydration in cement-based materials. Specific embodiments
[0036] The following embodiments are provided to better further understand the present invention, which is not limited to the best embodiment, and does not limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with those of other prior arts falls within the protection scope of the present invention.
[0037] For those not specifying specific experimental steps or conditions in the embodiments, the operations or conditions of the conventional experimental steps described in the literature in this field can be followed. For the reagents or instruments not indicating the manufacturer, they are all conventional reagent products that can be obtained through commercial purchase.
[0038] The polycarboxylate superplasticizer and S95-grade slag powder used in the examples and comparative examples of the present invention are both obtained commercially. Among them, the polycarboxylate superplasticizer is purchased from the polycarboxylate high-performance superplasticizer of Jiangsu Bote New Materials Co., Ltd., and the S95-grade slag powder is purchased from the S95-grade slag powder of Henan Borun Foundry Materials Co., Ltd.
[0039] Example 1
[0040] This example provides a preparation method of a composite early strength agent, including the following steps:
[0041] 1) Weigh the raw material components, which include: 1.2 kg of fly ash, 0.1 kg of hemihydrate gypsum, 0.4 kg of carbide slag, 0.1 kg of triethanolamine, 8.5 kg of water, and 0.07 kg of polycarboxylate superplasticizer; among them, the content of Al2O3 in the fly ash is 30 wt%, the content of Ca(OH)2 in the carbide slag is 79 wt%, and the water content in the carbide slag is 2 wt%.
[0042] 2) Mix the fly ash, hemihydrate gypsum, and carbide slag, and grind them in a ball mill. At the same time, slowly add triethanolamine for grinding assistance to obtain ground powder with a median particle size of 12 μm.
[0043] 3) Mix the ground powder obtained in step 2) with water and place it in a water bath stirring pot for heating reaction. The reaction temperature is 60 °C, the reaction time is 32 h, and the stirring speed during heating reaction is 200 rpm to obtain a reaction slurry. Use nuclear magnetic resonance (29Si-NMR) to detect that the reaction rate of the fly ash is 60%.
[0044] 4) Mix the reaction slurry obtained in step 3) with polycarboxylate superplasticizer, then grind it to a median particle size of 5.8 μm, and then adjust the solid content to 20% to obtain the composite early strength agent.
[0045] Example 2
[0046] This example provides a preparation method of a composite early strength agent, including the following steps:
[0047] 1) Weigh the raw material components, which include: 1.3 kg of fly ash, 0.3 kg of hemihydrate gypsum, 0.2 kg of carbide slag, 0.3 kg of triethanolamine, 8.2 kg of water, and 0.08 kg of polycarboxylate superplasticizer; among them, the content of Al2O3 in the fly ash is 32 wt%, the content of Ca(OH)2 in the carbide slag is 73 wt%, and the water content in the carbide slag is 2.5 wt%.
[0048] 2) Mix the fly ash, hemihydrate gypsum, and carbide slag, and grind them in a ball mill. At the same time, slowly add triethanolamine for grinding assistance to obtain ground powder with a median particle size of 12 μm.
[0049] 3) Mix the ground powder obtained in step 2) with water and place it in a water bath stirring pot for heating reaction. The reaction temperature is 60 °C, the reaction time is 30 h, and the stirring speed during heating reaction is 200 rpm to obtain a reaction slurry. Use nuclear magnetic resonance (29Si-NMR) to detect that the reaction rate of the fly ash is 62%.
[0050] 4) Mix the reaction slurry obtained in step 3) with polycarboxylate superplasticizer, then grind it to a median particle size of 6.0 μm, and then adjust the solid content to 20% to obtain the composite early strength agent.
[0051] Example 3
[0052] This example provides a preparation method of a composite early strength agent, which includes the following steps:
[0053] 1) Weigh the raw material components, which include: 1.4 kg of fly ash, 0.4 kg of hemihydrate gypsum, 0.1 kg of carbide slag, 0.4 kg of triethanolamine, 8.0 kg of water, and 0.06 kg of polycarboxylate superplasticizer; among them, the content of Al2O3 in the fly ash is 35 wt%, the content of Ca(OH)2 in the carbide slag is 70 wt%, and the moisture content in the carbide slag is 3 wt%.
[0054] 2) Mix the fly ash, hemihydrate gypsum, and carbide slag, and place them in a ball mill for grinding. At the same time, slowly add triethanolamine for grinding aid to obtain a ground powder with a median particle size of 12 μm.
[0055] 3) Mix the ground powder obtained in step 2) with water and place it in a water bath stirring pot for heating reaction. The reaction temperature is 60 °C, the reaction time is 24 h, and the stirring speed during the heating reaction is 200 rpm to obtain a reaction slurry. The reaction rate of the fly ash detected by nuclear magnetic resonance (29Si-NMR) is 65%.
[0056] 4) Mix the reaction slurry obtained in step 3) with the polycarboxylate superplasticizer, then grind it to a median particle size of 5.4 μm, and then adjust the solid content to 20% to obtain the composite early strength agent.
[0057] Example 4
[0058] This example provides a preparation method of a composite early strength agent, which includes the following steps:
[0059] 1) Weigh the raw material components, which include: 1.5 kg of fly ash, 0.2 kg of hemihydrate gypsum, 0.3 kg of carbide slag, 0.2 kg of triethanolamine, 7.8 kg of water, and 0.07 kg of polycarboxylate superplasticizer; among them, the content of Al2O3 in the fly ash is 32 wt%, the content of Ca(OH)2 in the carbide slag is 76 wt%, and the moisture content in the carbide slag is 2.8 wt%.
[0060] 2) Mix the fly ash, hemihydrate gypsum, and carbide slag, and place them in a ball mill for grinding. At the same time, slowly add triethanolamine for grinding aid to obtain a ground powder with a median particle size of 12 μm.
[0061] 3) Mix the ground powder obtained in step 2) with water and place it in a water bath stirring pot for heating reaction. The reaction temperature is 60 °C, the reaction time is 36 h, and the stirring speed during the heating reaction is 200 rpm to obtain a reaction slurry. The reaction rate of the fly ash detected by nuclear magnetic resonance (29Si-NMR) is 61%.
[0062] 4) Mix the reaction slurry obtained in step 3) with a polycarboxylate water reducer, then grind it to a median particle size of 5.9 μm, and then adjust the solid content to 20% to obtain the composite early strength agent.
[0063] Example 5
[0064] This example provides a preparation method of a composite early strength agent, including the following steps:
[0065] 1) Weigh the raw material components, and the raw material components include: 1.6 kg of fly ash, 0.1 kg of hemihydrate gypsum, 0.4 kg of carbide slag, 0.2 kg of triethanolamine, 7.5 kg of water, and 0.07 kg of polycarboxylate water reducer; among them, the content of Al2O3 in the fly ash is 30 wt%, the content of Ca(OH)2 in the carbide slag is 82 wt%, and the water content in the carbide slag is 3 wt%.
[0066] 2) Mix the fly ash, hemihydrate gypsum, and carbide slag, place them in a ball mill for grinding, and slowly add triethanolamine for grinding assistance to obtain a ground powder with a median particle size of 12 μm.
[0067] 3) Mix the ground powder obtained in step 2) with water and place it in a water bath stirring pot for heating reaction. The reaction temperature is 60 °C, the reaction time is 48 h, and the stirring speed during the heating reaction is 200 rpm to obtain a reaction slurry. Use nuclear magnetic resonance (29Si-NMR) to detect that the reaction rate of the fly ash is 68%.
[0068] 4) Mix the reaction slurry obtained in step 3) with a polycarboxylate water reducer, then grind it to a median particle size of 5.2 μm, and then adjust the solid content to 20% to obtain the composite early strength agent.
[0069] Comparative Example 1
[0070] This comparative example provides a preparation method of an early strength agent, including the following steps:
[0071] 1) Weigh the raw material components, and the raw material components include: 1.2 kg of fly ash, 0.1 kg of hemihydrate gypsum, 0.4 kg of carbide slag, 0.1 kg of triethanolamine, 8.5 kg of water, and 0.07 kg of polycarboxylate water reducer; among them, the content of Al2O3 in the fly ash is 30 wt%, the content of Ca(OH)2 in the carbide slag is 79 wt%, and the water content in the carbide slag is 2 wt%.
[0072] 2) Mix the fly ash, hemihydrate gypsum, carbide slag with water, place them in a water bath stirring pot for heating reaction. The reaction temperature is 60 °C, the reaction time is 32 h, and the stirring speed during the heating reaction is 200 rpm to obtain a reaction slurry. Use nuclear magnetic resonance (29Si-NMR) to detect that the reaction rate of the fly ash is 62%.
[0073] 3) Mix the reaction slurry obtained in step 2) with a polycarboxylate water reducer, then grind it to a median particle size of 5.8 μm, and then adjust the solid content to 20% to obtain the composite early strength agent.
[0074] Comparative Example 2
[0075] This comparative example provides a method for preparing an early strength agent, including the following steps:
[0076] 1) Weigh the raw material components, and the raw material components include: 1.2 kg of fly ash, 0.1 kg of hemihydrate gypsum, 0.4 kg of carbide slag, 0.1 kg of triethanolamine, 8.5 kg of water, and 0.07 kg of polycarboxylate water reducer; among them, the content of Al2O3 in the fly ash is 30 wt%, the content of Ca(OH)2 in the carbide slag is 79 wt%, and the moisture content in the carbide slag is 2 wt%;
[0077] 2) Mix the fly ash, hemihydrate gypsum, and carbide slag, place them in a ball mill for grinding, and slowly add triethanolamine for grinding assistance at the same time to obtain a ground powder with a median particle size of 12 μm;
[0078] 3) Mix the ground powder obtained in step 2) with water and place it in a water bath stirring pot, stir at 20 °C and 200 rpm for 32 h to obtain a reaction slurry, and use nuclear magnetic resonance (29Si-NMR) to detect that the reaction rate of the fly ash is 62%;
[0079] 4) Mix the reaction slurry obtained in step 3) with a polycarboxylate water reducer, then grind it to a median particle size of 5.8 μm, and then adjust the solid content to 20% to obtain the composite early strength agent.
[0080] This comparative example provides a method for preparing an early strength agent, which is different from Example 1 in that.
[0081] Comparative Example 3
[0082] This comparative example provides a method for preparing an early strength agent, including the following steps:
[0083] 1) Weigh the raw material components, and the raw material components include: 1.2 kg of fly ash, 0.1 kg of hemihydrate gypsum, 0.4 kg of carbide slag, 0.1 kg of triethanolamine, 8.5 kg of water, and 0.07 kg of polycarboxylate water reducer; among them, the content of Al2O3 in the fly ash is 30 wt%, the content of Ca(OH)2 in the carbide slag is 79 wt%, and the moisture content in the carbide slag is 2 wt%;
[0084] 2) Mix the fly ash, hemihydrate gypsum, and carbide slag, place them in a ball mill for grinding, and slowly add triethanolamine for grinding assistance at the same time to obtain a ground powder with a median particle size of 12 μm;
[0085] 3) Mix the ground powder obtained in step 2) with water, place it in a water bath stirring pot, and heat it for reaction. The reaction temperature is 60 °C, the reaction time is 32 h, and the stirring speed during heating reaction is 200 rpm to obtain a reaction slurry. The reaction rate of fly ash detected by nuclear magnetic resonance (29Si-NMR) is 62%;
[0086] 4) Mix the reaction slurry obtained in step 3) with a polycarboxylate superplasticizer, and then adjust the solid content to 20% to obtain the composite early strength agent.
[0087] Cementitious material Example 1
[0088] This example provides a sodium sulfate-activated slag cementitious material, the raw material components of which include: S95 slag powder, composite early strength agent and sodium sulfate. Among them, calculated according to the Na2O equivalent, the dosage of sodium sulfate reaches 4 wt% of the total mass of S95 slag powder for the mass of Na2O in sodium sulfate. The composite early strength agent is the composite early strength agent prepared in Example 1, and the dosage of the composite early strength agent is 3 wt% of the total mass of S95 slag powder.
[0089] Cementitious material Example 2
[0090] This example provides a sodium sulfate-activated slag cementitious material, the difference from Cementitious material Example 1 is only that the composite early strength agent is the composite early strength agent prepared in Example 2, and the dosage of the composite early strength agent is 5 wt% of the total mass of S95 slag powder.
[0091] Cementitious material Example 3
[0092] This example provides a sodium sulfate-activated slag cementitious material, the difference from Cementitious material Example 1 is only that the composite early strength agent is the composite early strength agent prepared in Example 3, and the dosage of the composite early strength agent is 4 wt% of the total mass of S95 slag powder.
[0093] Cementitious material Example 4
[0094] This example provides a sodium sulfate-activated slag cementitious material, the difference from Cementitious material Example 1 is only that the composite early strength agent is the composite early strength agent prepared in Example 4, and the dosage of the composite early strength agent is 3 wt% of the total mass of S95 slag powder.
[0095] Cementitious material Example 5
[0096] This example provides a sodium sulfate-activated slag cementitious material, the difference from Cementitious material Example 1 is only that the composite early strength agent is the composite early strength agent prepared in Example 5, and the dosage of the composite early strength agent is 5 wt% of the total mass of S95 slag powder.
[0097] Cementitious material Example 6
[0098] This embodiment provides a sodium sulfate-activated slag cementitious material, which is only different from the cementitious material in Embodiment 1 in that the composite early-strength agent is the composite early-strength agent prepared in Embodiment 1, and the dosage of the composite early-strength agent is 4wt% of the total mass of S95-grade slag powder.
[0099] Cementitious Material Embodiment 7
[0100] This embodiment provides a sodium sulfate-activated slag cementitious material, which is only different from the cementitious material in Embodiment 1 in that the composite early-strength agent is the composite early-strength agent prepared in Embodiment 2, and the dosage of the composite early-strength agent is 4wt% of the total mass of S95-grade slag powder.
[0101] Cementitious Material Embodiment 8
[0102] This embodiment provides a sodium sulfate-activated slag cementitious material, which is only different from the cementitious material in Embodiment 1 in that the composite early-strength agent is the composite early-strength agent prepared in Embodiment 3, and the dosage of the composite early-strength agent is 3wt% of the total mass of S95-grade slag powder.
[0103] Cementitious Material Embodiment 9
[0104] This embodiment provides a sodium sulfate-activated slag cementitious material, which is only different from the cementitious material in Embodiment 1 in that the composite early-strength agent is the composite early-strength agent prepared in Embodiment 4, and the dosage of the composite early-strength agent is 5wt% of the total mass of S95-grade slag powder.
[0105] Cementitious Material Embodiment 10
[0106] This embodiment provides a sodium sulfate-activated slag cementitious material, which is only different from the cementitious material in Embodiment 1 in that the composite early-strength agent is the composite early-strength agent prepared in Embodiment 5, and the dosage of the composite early-strength agent is 4wt% of the total mass of S95-grade slag powder.
[0107] Cementitious Material Comparative Example 1
[0108] This comparative example provides a sodium sulfate-activated slag cementitious material, the raw material components of which include: S95-grade slag powder and sodium sulfate. Among them, calculated according to the Na2O equivalent, the dosage of sodium sulfate reaches 4wt% of the mass of Na2O in sodium sulfate accounting for the total mass of S95-grade slag powder.
[0109] Cementitious Material Comparative Example 2
[0110] This comparative example provides a sodium sulfate-activated slag cementitious material, which is only different from the cementitious material in Embodiment 1 in that the composite early-strength agent is the composite early-strength agent prepared in Comparative Example 1.
[0111] Cementitious Material Comparative Example 3
[0112] This comparative example provides a sodium sulfate-activated slag cementitious material, which is only different from Example 1 of the cementitious material in that the compound early-strength agent is the compound early-strength agent prepared in Comparative Example 2.
[0113] Cementitious material Comparative Example 4
[0114] This comparative example provides a sodium sulfate-activated slag cementitious material, which is only different from Example 1 of the cementitious material in that the compound early-strength agent is the compound early-strength agent prepared in Comparative Example 3.
[0115] Test example
[0116] Take the sodium sulfate-activated slag cementitious materials of Examples 1-10 of the cementitious material and Comparative Examples 1-4 of the cementitious material as cement, prepare samples with reference to the "Test Method for Strength of Cement Mortar" (GB / T 17671-2021), and place the formed samples in the curing room for curing. When the age reaches, carry out the compressive strength test. The 1d and 28d strengths of the samples and their strength growth rates relative to Comparative Example 1 are shown in Table 3.
[0117] Table 3 1d and 28d strengths and strength growth rates of the samples
[0118]
[0119]
[0120] As can be seen from Table 3, when the compound early-strength agent of the present invention is incorporated into the sodium sulfate-activated slag cementitious material system at 3-5% of the total mass of S95-grade slag powder, its early strength is greatly improved. Compared with Comparative Example 1, its 1d strength is increased by more than 1 time; and this kind of early-strength agent is based on fly ash, and the pozzolanic reaction occurring in the later stage of hydration also contributes to its later strength, and its 28d strength is increased by more than 50%. The present invention proposes a fly ash-based compound early-strength agent for sodium sulfate-activated slag cementitious materials, which is expected to solve the common industry problem of poor early mechanical properties of this type of cementitious material and improve the application of sodium sulfate-activated slag cementitious materials in the engineering field.
[0121] Obviously, the above-mentioned embodiments are only examples clearly described and not limitations on the implementation manners. For those of ordinary skill in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation manners here. And the obvious changes or modifications derived therefrom are still within the protection scope of the present invention.
Claims
1. A preparation method of a composite early strength agent, characterized in that, It includes the following steps: 1) Weigh the raw materials, which include fly ash, hemihydrate gypsum, carbide slag, triethanolamine, polycarboxylate water reducer and water; 2) Mix fly ash, hemihydrate gypsum and carbide slag, add triethanolamine and grind to obtain ground powder; 3) Mix the ground powder obtained in step 2) with water and heat for reaction to obtain reaction slurry; 4) Mix the reaction slurry obtained in step 3) with polycarboxylate water reducer, and then grind to obtain the composite early strength agent.
2. The preparation method of the composite early strength agent according to claim 1, characterized in that, The raw materials in step 1), by weight, include: 12-16 parts of fly ash, 1-4 parts of hemihydrate gypsum, 1-4 parts of carbide slag, 0.8-1.5 parts of triethanolamine, 0.6-0.8 parts of polycarboxylate water reducer and 75-85 parts of water; The content of Al2O3 in the fly ash is ≥30wt%; The content of Ca(OH)2 in the carbide slag is ≥70wt% and the moisture content is ≤3wt%.
3. The preparation method of the composite early strength agent according to claim 1 or 2, characterized in that The median particle size of the ground powder in step 2) is not greater than 12μm; Optionally, the median particle size of the ground powder in step 2) is 10-12μm; Optionally, the grinding is selected from ball milling.
4. The preparation method of the composite early strength agent according to any one of claims 1-3, characterized in that, The temperature of the heating reaction in step 3) is 50-70°C and the heating reaction time is 24-48h; Optionally, the heating reaction is carried out under stirring conditions, and the stirring speed is 100-200rpm; The reaction rate of the fly ash in step 3) is ≥60%; Optionally, the reaction rate of the fly ash in step 3) is 60-70%.
5. The preparation method of the composite early strength agent according to any one of claims 1-4, characterized in that, In step 4), grind to a median particle size not greater than 6μm; Optionally, the grinding is selected from ball milling; Optionally, in step 4), grind to a median particle size of 5-6μm.
6. The preparation method of the composite early strength agent according to any one of claims 1-5, characterized in that, After the grinding step in step 4), there is also a step of adjusting the solid content; Optionally, after the grinding step in step 4), adjust the solid content to 18-22% to obtain the composite early strength agent.
7. A composite early strength agent, characterized in that, It is prepared by the preparation method of the composite early strength agent according to any one of claims 1-6.
8. A sodium sulfate-activated slag cementitious material, characterized in that, The sodium sulfate-activated slag cementitious material includes the composite early strength agent according to claim 7.
9. The sodium sulfate-activated slag cementitious material according to claim 8, wherein The mass content of the composite early strength agent in the sodium sulfate-activated slag cementitious material is 3-5wt%.
10. Application of the composite early strength agent according to claim 7 or the sodium sulfate-activated slag cementitious material according to claim 8 or 9 in building materials.